Lo, Irving Yucheng y William Schultz (eds.), Waiting for the Unicorn: Poems and Lyrics of China's Last Dynasty, 1644-1911, Indiana University Press, 1986, pp. xxvii + 423. - Maeth Ch., Russell (Estudios de Asia y África, 1988)
-